Bounded Mobilities Ethnographic Perspectives on Social Hierarchies and Global Inequalities - Götz, Irene; Gutekunst, Miriam; Hackl, Andreas (Kultur und soziale Praxis, 2016)
Mobility is a keyword of late modernity that suggests an increasingly unrestrained and interconnected world of individual opportunities. However, as privileges enable some to live in a seemingly borderless world, others remain excluded and marginalized. Boundaries are created, modified and consolidated, particularly in times of hypermobility. Evidently, mobility is closely tied to immobility.This volume features ethnographic research that challenges the concept of mobility with regard to social inequalities and global hierarchies